Successful leadership in academic medicine - Greer, David M. 1966- (Cambridge University Press, 2022)
Good leadership in medicine is crucial, but unfortunately, often woefully inadequate. Those chosen to lead often have limited experience in leadership themselves, or worse, are appointed because of achievements that have nothing to do with their ability to lead. Serving as a guide for those in, or considering, leadership positions in medicine, this book demonstrates how to play to one's strengths and effectively recognise and overcome weaknesses. Describing how to form a functional team, and align your goals with those of upper leadership, advice is applicable to all disciplines and hierarchy structures. The author, David Greer, is a renowned clinician and educator, and has held department chair positions in several prestigious institutions, positioning him perfectly to educate on the qualities of a successful leader. Readers will learn how to work within a team, manage unforeseen crises and to embrace mistakes as opportunities for growth